Anti-Inflammatory and Anti-Hyperuricemic Effects of Chrysin in a Rat Model of High Fructose Corn Syrup Induced Hyperuricemia - Tahany, Hanifah; Parisa, Nita; Nugraha, M Daffa; Harahap, Debby Handayati; Theodorus, Theodorus (Biomedical Journal of Indonesia, 2025)
An increase in the blood level of uric acid, or hyperuricemia, is a disorder that can cause damage to the kidneys and gout among other health problems. Worldwide, the incidence of hyperuricemia has been rising, in part because of dietary factors such the use of HFCS, a prevalent sweetener found in processed foods. Thus, research into natural substances with anti-inflammatory and anti-hyperuricemia attributes, such as chrysin, is critical to the fields of therapeutic and preventive medicine. This study investigates the anti-inflammatory and anti-hyperuricemic effects of chrysin in a rat model of hyperuricemia induced by high-fructose corn syrup. The research reveals that chrysin exerts its therapeutic effects through antioxidant activity and the inhibition of inflammatory signaling pathways, resulting in a decrease in oxidative stress and the expression of the pro-inflammatory cytokine IL-1β. Treatment with chrysin leads to a significant increase in tissue weight, tissue index, and kidney histology, indicating its potential in mitigating kidney damage associated with hyperuricemia. The study demonstrates a dose-dependent reduction in IL-1β levels and inflammation activation with chrysin treatment, surpassing the anti-inflammatory effects of the comparison group. Furthermore, chrysin treatment reduces malondialdehyde concentration and mitigates the activation of inflammasome-related protein induced by high-fructose corn syrup. These findings highlight the promising therapeutic potential of chrysin in managing hyperuricemia and related metabolic disorders.